Performance of Friesian and Brown Swiss Cows Raised on the University Farm in Tripoli - DARWASH, ADNAN O. (The Libyan Journal of Agriculture, 2023)
The performance of Friesian and Brown Swiss cows, imported from Holland and Austria respectively, was studied. A total of 159 calvings and 141 lactations for both breeds were described. Milk production of Friesian cows was higher than that attained by the Brown Swiss throughout the five lactations. It was 4,205, 4,496, 4,827, 4,970. 4.355 Kilograms for the Friesians and 3,163, 3,466.4.043,4.058.4.043 kgs for the Brown Swiss during the 1 st, 2nd. 3rd. 4th and 5th lactation, respectively. The difference between production means was significant (P<,01) during the first two lactations. Butter Fat production was 3.25, 3.34. 3.15, 2.82, 2.59% for the Friesians and 3.45, 3.18, 3.35, 3.16, 3.43% for the Brown Swiss during the five lactations, respectively. The difference in fat production between the two breeds was not statistically significant. The duration of lactations was within the normal range of 10 months. It was 319.3, 302.8, 301.7, 287.8, 285.0 days for the Friesians and 292.6. 293.3. 310.8, 271.0. 325.5 days for the Brown Swiss cows during the five lactations, respectively. The difference in the length of lactations between breeds was not statistically significant. Age at freshening of Friesian cows was significantly lower than that of the Brown Swiss (P < .01). It was 25.3 months for the Friesians and 29.4 months for Brown Swiss cows.